Resource-Use Efficiency in Public Schools: A Study of Connecticut Data - Ray, Subhash C. (Management Science, 1991)
This study combines Data Envelopment Analysis (DEA) with regression modelling to estimate relative efficiency in the public school districts of Connecticut. Factors affecting achievements are classified as school inputs and other socio-economic factors. DEA is performed with the school inputs only. Efficiency measures obtained from DEA are subsequently related to the socio-economic factors in a regression model with a one-sided disturbance term. The findings suggest that while productivity of school inputs varies considerably across districts this can be ascribed to a large extent to differences in the socio-economic background of the communities served. Variation in managerial efficiency is much less than what is implied by the DEA results.